2016
DOI: 10.1038/srep38226
|View full text |Cite
|
Sign up to set email alerts
|

Sequential information in a great ape utterance

Abstract: Birdsong is a prime example of acoustically sophisticated vocal behaviour, but its complexity has evolved mainly through sexual selection to attract mates and repel sexual rivals. In contrast, non-human primate calls often mediate complex social interactions, but are generally regarded as acoustically simple. Here, we examine arguably the most complex call in great ape vocal communication, the chimpanzee (Pan troglodytes schweinfurthii) ‘pant hoot’. This signal consists of four acoustically distinct phases: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 77 publications
2
46
3
Order By: Relevance
“…These results imply trade-offs in investment into different phases. Previous analyses of pant hoots suggest that prolonging the duration of particular phases, such as the build-up or the climax, may be used as effective territorial displays or to coordinate chorusing [ 29 , 43 ]. However, it appears that, in some cases, if one phase is longer in total duration, the subsequent one tends to be shorter; thus, plasticity in phase duration appears somewhat constrained at a broader level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results imply trade-offs in investment into different phases. Previous analyses of pant hoots suggest that prolonging the duration of particular phases, such as the build-up or the climax, may be used as effective territorial displays or to coordinate chorusing [ 29 , 43 ]. However, it appears that, in some cases, if one phase is longer in total duration, the subsequent one tends to be shorter; thus, plasticity in phase duration appears somewhat constrained at a broader level.…”
Section: Discussionmentioning
confidence: 99%
“…At a functional level, the different relationships between call F0 and duration found in different phases suggest that specific phases within a pant hoot have distinct functions modulated by their pitch [ 43 ]. For example, the low-frequency build-up phase seems to be directed (at least in part) to the nearby individuals, since callers adjust its duration depending on the vocal response of the nearby males [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, vocalisation, the active generation of sounds with specific organs, becomes an expression of an internal state of an animal generated spontaneously or motivated by an external event [ 20 ]. Many of these vocalisations have a complex structure that includes different acoustic elements and there are many hypotheses related to the adaptive function of how such complexity [ 21 ] have developed over years. The study of emotions in animals is related to the evolution of species and consequently to the evolution of animal vocalisations.…”
Section: Related Workmentioning
confidence: 99%
“…Although not yet studied systematically, the calls given as part of the four units almost certainly contribute to other constructions in chimpanzee vocal behaviour or are produced as standalone signals (P Fedurek, personal communication). In a study using machine learning, it was demonstrated that the four units convey information on caller identity, rank and age, and on the external event [36]. The different call types within the four units can be repeated multiple times, but it is currently unknown whether this has communicative function.…”
Section: Merged Compoundsmentioning
confidence: 99%